Preference Constellations in EU–Russian Crisis Bargaining over Syria and Ukraine - Jonas J. Driedger; Ulrich Krotz (JCMS: Journal of Common Market Studies, 2023)
The Russian invasion of Ukraine in early 2022 and the ensuing EU–Russian clash over the fate of Ukraine highlight the importance of explaining the outcomes of EU–Russian crisis bargaining. Complementing existing accounts, we argue that favourable preference constellations are key: The more determined, united and focused side prevails over its less interested, divided or unfocused counterpart. We first establish the inferiority of Russia's influence assets (economic, military, normative and allies) relative to the EU. We then use congruence analysis to reverse-engineer crisis bargaining outcomes in key cases of EU–Russian crisis bargaining, showing that favourable preference constellations allowed Russia, despite inferior assets and EU opposition, to ensure Syrian dictator Assad's political survival, finalize the annexation of Crimea in 2014 and keep Donbass out of Kyiv's control since then. Finally, we discuss the implications of these findings for related areas, as well as for current and future EU–Russian crisis bargaining, specifically over Ukraine.
Keywords: 330; crisis bargaining; EU foreign and security policy; EU-Russian relations; Syria; Ukraine